Adjuvant treatment modalities for gastric cancer - Kilic, Leyla; Ordu, Cetin (Nova Science Publishers, Inc., 2014)
Gastric cancer is a leading cause of cancer-related death and thus represents a significant global health concern. Surgical resection remains the only effective curative treatment of gastric cancer. Less than 40% of cases will be able to be cured with complete surgical resection of tumor. In patients with advanced T3-4 tumors and/or tumor-positive lymph nodes the relapse and death rates from recurrent cancer exceed 70-80%. Because of high incidence of locoregional recurrence, adjuvant and neoadjuvant treatment modalities are crucial. Following the results of Intergroup trial (INT-0116) twelve years ago and the update of ten years outcome of study with still improvement of overall survival (OS) and disease free survival (DFS), chemoradiotherapy became standart adjuvant treatment modality in operated gastric cancer. Alternative trials have been reproduced without direct comparison to the approach established by INT-0116. The Japanese ACTS-GC (Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer) study demonstrated a 33% improvement in OS for patients receiving 1 year of postoperative adjuvant S-1, an oral fluoropyrimidine. In South Korea, Japan, and Taiwan, the CLASSIC (Adjuvant Capecitabine and Oxaliplatin for Gastric Cancer After D2 Gastrectomy) study reported a 44% improvement in DFS for patients randomly assigned to postoperative capecitabine and oxaliplatin (XELOX) when compared with observation. Both ACTS-GC and CLASSIC limited enrollment to patients who had undergone a D2 lymph node dissection which is a common technique for gastric cancer surgery in Asia. However, limited D0 or D1dissections are more widespread in the United States. Thus, the benefit of radiotherapy in the adjuvant setting for D0 and D1 dissections is a subject of debate. According to current guidelines, adjuvant chemotherapy is an option for only D2 lymph node dissections. Two recently completed trials have directly compared different postoperative adjuvant regimens. The ARTIST (Adjuvant Chemoradiation Therapy in Stomach Cancer) trial compared postoperative capecitabine and cisplatin (XP) to chemoradiotherapy (XP plus radiotherapy with capecitabine) in patients with curative gastrectomy with D2 dissection. Although the addition of radiotherapy to postoperative chemotherapy did not significantly improve DFS among all enrolled subjects, in subgroup analyses, patients with node-positive disease did experience a superior DFS. Ultimately, beyond the primary objectives of these proposed and ongoing trials, we must continue to identify new prognostic and predictive factors, such as human epidermal growth factor receptor 2 overexpression or diffuse histology in adjuvant setting, that may serve as the basis for more effective, tailored therapeutic approaches in patients with gastric adenocarcinoma. © 2014 Nova Science Publishers, Inc.